The running engagement and motivation of Filipino young adult recreational runners a correlational study on the running modality and total running time - Aguirre, Justine Marie Ileani R.
Physical inactivity has been a challenge which can harm the Filipinos’ health and well-being. This correlational research investigated the relationship between the running modality, and the running duration and frequency. Moreover, it also determined the running motivations of Filipino young adult recreational runners. Using the convenience sampling method, this research gathered data from physically active Filipinos aged 18 to 26 who are part of the running community in University of the Philippines Diliman. The participants answered an online survey–which includes the Eindhoven Running Survey 2016 and the Exercise Motivations Inventory-2 (EMI-2)–consisting of some questions on demographics and running engagements. SPSS was used, with a significance level of α = 0.05, to conduct the Rank-Biserial Correlation that determined the relationships among running modality and total running time. The data showed that Filipino young adult recreational runners who run alone have more total running time. However, the results were not statistically significant. A content analysis was also conducted to identify running motivation themes and patterns. It was discovered that Positive Health, Weight Management, Ill-Health Avoidance, Strength & Endurance, and Enjoyment were the main motivations for Filipino young adults to engage in recreational running. The results provided insights into the correlation between the running modality to the total running minutes, further influencing Filipino young adult recreational runners and offering practical applications for professionals in the fitness field, the University of the Philippines Diliman, and the sports organizations and government to promote physical activity.